2018
DOI: 10.1089/lap.2017.0511
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Adolescent and Young Adults Receiving High Ligation and Mesh Repairs: A 16-Year Experience

Abstract: In adolescents and young adults, the long-term recurrence rate after inguinal hernia repair is ∼6% with time to recurrence approaching 4 years. Outcomes of high ligation and mesh repair are similar, highlighting the need for individualized approaches for this unique population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 32 publications
0
17
0
Order By: Relevance
“…After 24-119months (mean 73.56 ± 28.56months)of follow-up, the results showed the recurrence rate was 0%. some other studies have shown that the recurrence rate of high hernia sac ligation without mesh for adolescent hernias was 0.95%-3.5%, which was also relatively low [7,18].The recurrence rate of high ligation for adolescent hernias was similar to that of mesh repair for adult hernias [19].Another study reported that the recurrence rate of patients aged 18-25 years who underwent herniectomy without mesh placement or posterior wall repair is 0% [20]. These suggests that high hernia sac ligation without mesh placement or posterior wall repair is effective enough in treating adolescent hernias.However, none of these studies showed the size of the deep ring of the indirect hernia, as the size of the internal ring may affect the choice of the surgeon [17,21].The internal ring is small, the surgeon chooses the hernia sac high ligation more, the internal ring is large, and the surgeon chooses the mesh repair or tissue repair more.So how large the internal ring should the surgeon select mesh repair or tissue repair?How small select a simple high hernia sac ligation?…”
Section: Discussionmentioning
confidence: 83%
“…After 24-119months (mean 73.56 ± 28.56months)of follow-up, the results showed the recurrence rate was 0%. some other studies have shown that the recurrence rate of high hernia sac ligation without mesh for adolescent hernias was 0.95%-3.5%, which was also relatively low [7,18].The recurrence rate of high ligation for adolescent hernias was similar to that of mesh repair for adult hernias [19].Another study reported that the recurrence rate of patients aged 18-25 years who underwent herniectomy without mesh placement or posterior wall repair is 0% [20]. These suggests that high hernia sac ligation without mesh placement or posterior wall repair is effective enough in treating adolescent hernias.However, none of these studies showed the size of the deep ring of the indirect hernia, as the size of the internal ring may affect the choice of the surgeon [17,21].The internal ring is small, the surgeon chooses the hernia sac high ligation more, the internal ring is large, and the surgeon chooses the mesh repair or tissue repair more.So how large the internal ring should the surgeon select mesh repair or tissue repair?How small select a simple high hernia sac ligation?…”
Section: Discussionmentioning
confidence: 83%
“…Two randomized controlled trials [ 34 , 37 ], six prospective cohort studies [ 26 , 38 40 , 43 , 44 ] and 13 retrospective cohort studies [ 27 33 , 35 , 36 , 41 , 42 , 45 , 46 ] with data on a total of 3,816 adolescent patients with 3,953 groin hernia repairs were included. Overall, there were 3,200 non-mesh and 753 mesh repairs.…”
Section: Resultsmentioning
confidence: 99%
“…4,6,9,14 Previous reports have revealed a similar or lower hernia recurrence after mesh repair in young adults than those without mesh. 4,6,13,14,17 Tanaka et al reported that high ligation of a hernia orifice is insufficient for all young adult patients. 6 However, laparoscopic high ligation has some merits, such as cosmetic advantages, less peritoneal damage, and a lack of mesh complications, and it is easy to repair an inguinal hernia recurrence after a laparoscopic high ligation procedure.…”
Section: Resultsmentioning
confidence: 99%
“…After laparoscopic high ligation in adolescents and young adults, recurrence is 0%–5.9% 4,6,9,14 . Previous reports have revealed a similar or lower hernia recurrence after mesh repair in young adults than those without mesh 4,6,13,14,17 . Tanaka et al.…”
Section: Discussionmentioning
confidence: 96%